Effect of Functionalized Silica Nanoparticles on the Mass Transfer Process in Active Pla Nanocomposite Films Obtained by Supercritical Impregnation for Sustainable Food Packaging - Rodriguez-Mercado, F; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Riveros-Faba, S; Villegas-Vallejos, C (Elsevier B.V., 2020)
Nanocomposite films based on PLA with 1.0 % w/w silica nanoparticles (NP) and surface-functionalized silica nanoparticles with lactic acid (NP-LA), respectively, were obtained by extrusion process. Subsequently, cinnamaldehyde (ci) was incorporated through supercritical impregnation in the films at a pressure of 12 MPa, 40 °C temperature and 1.0 MPa min−1 depressurization rate. The developed materials were characterized on their thermal-mechanical, structural and barrier properties. Simultaneously, a phenomenological mass transfer was used to describe the release of cinnamaldehyde from the bionanocomposite in an aqueous food simulant (ethanol 10 % v/v solution). A 44 % decrease in oxygen permeability concerning the material without nanoparticles was checked as well as the plasticizing effect of cinnamaldehyde. Regarding the release of the active compound, the incorporation of functionalized nanoparticles NP-LA decreased the diffusion coefficient from 3.5·10−14 to 0.9·10−14 (m2/s), obtaining the filling effect of the silica nanoparticles, delaying the active compound release. © 2020 Elsevier B.V.